Biological characterisation, expression and functional analysis of non-specific cytotoxic cell receptor protein 1 in Nile tilapia (Oreochromis niloticus). Issue 104 (September 2020) - Huang, Yu; Liu, Xinchao; Cai, Jia; Tang, Jufen; Cai, Shuanghu; Lu, Yishan; Wang, Bei; Jian, Jichang
Abstract: Non-specific cytotoxic cell receptor protein 1 (NCCRP-1) plays a role in recognition of target cell and activation of non-specific cytotoxic cell (NCC). In this study, the full length of Nile tilapia NCCRP-1 (On-NCCRP-1) was cloned. cDNA is composed of 1045 bp with a 90 bp of 5′-Untranslated Regions (UTR), 702 bp open reading frame (ORF) and 253 bp 3′-UTR, encoding 233 amino acids (GenBank accession no: MF162296 ). The On-NCCRP-1 genomic sequence is 4471 bp in length and contains six exons and five introns. On-NCCRP-1 possesses some inherent conservative domains, such as proline-rich motifs, antigen recognition site, and F-box-related domain. Subcellular localisation and Western blot analysis indicated that On-NCCRP-1 is located in the cell membrane. The transcript of On-NCCRP-1 was detected in all the examined tissues of healthy Nile tilapia by using qRT-PCR, with the highest expression levels in the liver. Following Streptococcus agalactiae challenged in vivo, the On-NCCRP-1 expression was up-regulated significantly in brain, intestines, head kidney and spleen. In the in vitro analysis, the On-NCCRP-1 expression in NCCs was up-regulated significantly from 8 h to 12 h after LPS challenge, and up-regulated significantly at 12 h after challenged with polyI:C. After NCCs were challenged with inactivated S. agalactiae, the On-NCCRP-1 expression was down-regulated significantly after 24 h. NF-кB pathway was strongly activated by the over-expression of On-NCCRP-1 in HEK-293T cells. These results indicate that On-NCCRP-1, as a membrane surface receptor of NCCs, may play an important role in immune response to pathogenic infection in Nile tilapia. Graphical abstract: Image 1 Highlights: Complete cDNA and genomic sequence of On-NCCRP-1 was identified in Oreochromis niloticus. On-NCCRP-1 could located in the cell membrane of NCC. S. agalactiae could significantly induce On-NCCRP-1 mRNA expression in vivo or vitro. Over-expression of On-NCCRP-1 could strongly activated NF-кB pathway.